Gerakan Laki-laki Sadar Stunting untuk Mencegah Stunting dan Mewujudkan Generasi Sehat Desa Lembuak, Kecamatan Narmada, Lombok Barat - Hayati Hayati; Arifuddin Sahidu; Muktasam Muktasam (Universitas Mataram, 2023)
Stunting is currently still a public health problem related to chronic malnutrition. Stunting cases also occur in Narmada District, West Lombok Regency, which has productive rice fields, livestock and poultry can develop well. The still high number of stunting cases is related to low nutritional intake, unequal gender roles in household food security and efforts to prevent stunting in the household. This community service activity (PKM) is aimed at raising awareness among men as part of society, religious leaders and community leaders regarding stunting and efforts to prevent it. Apart from that, this PKM activity is also aimed at optimizing the role of religious leaders, community leaders and youth leaders in carrying out stunting awareness outreach and prevention efforts to the community, especially men. The method for implementing extension activities is carried out in stages, namely the first stage at the village level and the second stage at the hamlet level. The method used is a participatory counseling method, namely brainstorming, participatory lectures, questions and answers, discussions and practice. The implementation of extension activities ran smoothly and effectively. There has been an increase in knowledge and a growing positive attitude towards extension materials. This is demonstrated by the compilation of a collection of outreach materials (Pocket Books), the enthusiastic attitude of local resource persons and the active feedback/participation of participants during the question and answer sessions and discussions.